Brief intervention on Smoking, Nutrition, Alcohol and Physical (SNAP) inactivity for smoking relapse prevention after release from smoke-free prisons: a study protocol for a multicentre, investigator-blinded, randomised controlled trial. Issue 10 (18th October 2018) - Jin, Xingzhong; Kinner, Stuart A; Hopkins, Robyn; Stockings, Emily; Courtney, Ryan J; Shakeshaft, Anthony; Petrie, Dennis; Dobbins, Timothy; Dolan, Kate
Abstract : Introduction: Smoking remains the leading risk factor for disease burden and mortality worldwide. Heavy Smoking is often associated with poor Nutrition, Alcohol abuse and Physical inactivity (known as 'SNAP'). Australia's first prison smoking ban was introduced in the Northern Territory in July 2013. However, relapse to smoking after release from prison is normative. Holistic and cost-effective interventions are needed to maintain post-release abstinence to realise the potential public health impact of smoke-free prison policies. Rigorous, large-scale trials of innovative and scalable interventions are crucial to inform tobacco control policies in correctional settings. Methods and analysis: This multicentre, investigator-blinded, randomised parallel superiority trial will evaluate the effectiveness of a brief intervention on SNAP versus usual care in preventing smoking relapse among people released from smoke-free prisons in the Northern Territory, Australia. A maximum of 824 participants will be enrolled and randomly assigned to either SNAP intervention or usual care at a 1:1 ratio at baseline. The primary endpoint is self-reported continuous smoking abstinence three months after release from prison, verified by breath carbon monoxide test. Secondary endpoints include seven-day point prevalence abstinence, time to first cigarette, number of cigarettes smoked post release, Health Eating Index for Australian Adults, Alcohol Use Disorder Identification Test-Consumption and International Physical Activity Questionnaire scores. The primary endpoint will be analysed on an intention-to-treat basis using a simple log binomial regression model with multiple imputation for missing outcome data. A cost-effectiveness analysis of the brief intervention will be conducted subsequently. Ethics and dissemination: This study was approved by the University of New South Wales Human Research Ethics Committee (HREC), Menzies HREC and Central Australia HREC. Primary results of the trial and each of the secondary endpoints will be submitted for publication in a peer-review journal. Trial registration number: ACTRN12617000217303; Pre-results.